STRATEGI PENYULUHAN DAN KOMUNIKASI PERTANIAN DALAM MERUBAH PARADIGMA PETANI PADA PENERAPAN SISTEM JAJAR LEGOWO DI KECAMATAN DUNGALIYO KABUPATEN GORONTALO - Gaib, Siswan Y; Rauf, Asda; Saleh, Yanti (AGRINESIA : Jurnal Ilmiah Agribisnis, 2017)
This research aims to 1) investigate attitude and behavior of farmers in adopting information of extension man related to legowo row planting system in Sub-district of Dungaliyo; 2) identify internal and external factor which influence farmers in implementing legowo row planting system in Sub-district of Dungaliyo; and 3) compile strategy of counseling and agricultural communication in the implementation of legowo row planting system in Sub-district of Dungaliyo. The research applies survey method and it is conducted from April to May 2017. The aplied data analysis are descripteve and SWOT. Research samples are 54 respondents that are determined by purposive sampling. Research finding reveal that 1) implementation of legowo row planting system achieves positive response from majority of farmers in Sub-district of Dungaliyo, District of Gorontalo. Ther are 34 respondents or 62,97% out of 54 have implemented also this as it is profitable while the rest 20 respondents or 37,03% have implemented also the system only for trial; 2) internal factors are age, status of land, knowledge of farmers about advantage of legowo row planting system while external factors are role of counseling institution, support of government, alsintan aid and production facility; 3) strategy of counseling in the imlementation of legowo row planting system is through diagram of SWOT analysis which elaborates that its strength is greater than its weakness, it creates X axis in diagram SWOT and it is in quadrant I which means that it supports aggressive strategy or SO (Strength-Opportunities) strategy, very profitable situation since it has strength and opportunity that can be used as good and as much as possible.